Social Assistance, Labor and Anti-Communism during the Cold War: Theresita Porto da Silveira's Conservative Feminism, 1939-1971 - Nunes, Guilherme Machado [UNESP] (Programa Pos-graduacao Historia Univ Estado Do Rio De Janeiro, 2024)
Theresita Porto da Silveira was a journalist and the director of the Technical School of Social Service in Rio de Janeiro from 1938 to 1967. She participated in events abroad and engaged with various members of the Brazilian State. In 1946, she established a Brazilian National Committee for the Women's International League for Peace and Freedom (WILPF), a transnational feminist organization based in Geneva. Theresita identified herself as a feminist and indeed contributed to expanding spaces for women's advancement. However, her perspective was quite conservative: she believed that women were responsible for the home, and she was anti-communist and upheld Christian values as the standard for women. Based on the letters she exchanged with LIMPL and articles she published in newspapers, this article presents a biographical study of Theresita Porto da Silveira that explores the limits and possibilities of action for an upper-middle-class white woman in that time and analyzes how these characteristics shaped her feminist activism.
Keywords: Feminism; Biography; WILPF; Social Assistance; Cold War